Alterations in immune and renal biomarkers among workers occupationally exposed to low levels of trichloroethylene below current regulatory standards. Issue 6 (10th April 2019) - Lee, Kyoung-Mu; Zhang, Luoping; Vermeulen, Roel; Hu, Wei; Bassig, Bryan A; Wong, Jason JJ; Qiu, Chuangyi; Purdue, Mark; Wen, Cuiju; Walker, Douglas I; Jones, Dean P; Li, Laiyu; et al.
Abstract : Objectives: The occupational exposure limit for trichloroethylene (TCE) in different countries varies from 1 to 100 ppm as an 8-hour time-weighted average (TWA). Many countries currently use 10 ppm as the regulatory standard for occupational exposures, but the biological effects in humans at this level of exposure remain unclear. The objective of our study was to evaluate alterations in immune and renal biomarkers among workers occupationally exposed to low levels of TCE below current regulatory standards. Methods: We conducted a cross-sectional molecular epidemiology study of 80 healthy workers exposed to a wide range of TCE (ie, 0.4–229 ppm) and 96 comparable unexposed controls in China, and previously reported that TCE exposure was associated with multiple candidate biological markers related to immune function and kidney toxicity. Here, we conducted further analyses of all of the 31 biomarkers that we have measured to determine the magnitude and statistical significance of changes in the subgroup of workers (n=35) exposed to <10 ppm TCE compared with controls. Results: Six immune biomarkers (ie, CD4+ effector memory T cells, sCD27, sCD30, interleukin-10, IgG and IgM) were significantly decreased (% difference ranged from −16.0% to −72.1%) and one kidney toxicity marker (kidney injury molecule-1, KIM-1) was significantly increased (% difference: +52.5%) among workers exposed to <10 ppm compared with the control group. These associations remained noteworthy after taking into account multiple comparisons using the false discovery rate (ie, <0.20). Conclusion: Our results suggest that occupational exposure to TCE below 10 ppm as an 8-hour TWA may alter levels of key markers of immune function and kidney toxicity.